Development of market-oriented strategies through cross-functional integration in the context of the food and beverage industry - Murillo Oviedo, Ana Beatriz (2020)
The objective of this study is to analyze how cross-functional integration contributes to the development of market-oriented strategies in the context of food and beverage manufacturers in Latin America. A multi-case study was conducted in two multinational companies in Costa Rica and Brazil. Twenty-four semi-structured interviews were carried out with managers, leaders and supervisors. The results showed four market-oriented processes: Product launch, Product delivery, Customer complaints solution, and Improvement and innovation projects. Within these processes, twelve integration factors that impact market orientation were characterized. They also indicate that the concepts of Market orientation and Cross-functional integration should be integrated in the organizational culture to facilitate the understanding of the different needs and levels of urgency. The studied literature does not emphasize the way integration is operationalized to allow organizations to be market-oriented. According to our findings, responsive strategies depend on the integration of various internal functions to generate market intelligence. Managers must realize that when the workers are motivated and informed, they become more willing to take on a group vision and commit to organizational goals. This paper presents seven propositions on the operationalization of market orientation through cross-functional integration.